2019
DOI: 10.3390/rs11242980
|View full text |Cite
|
Sign up to set email alerts
|

TanDEM-X Forest Mapping Using Convolutional Neural Networks

Abstract: In this work, we face the problem of forest mapping from TanDEM-X data by means of Convolutional Neural Networks (CNNs). Our study aims to highlight the relevance of domain-related features for the extraction of the information of interest thanks to their joint nonlinear processing through CNN. In particular, we focus on the main InSAR features as the backscatter, coherence, and volume decorrelation, as well as the acquisition geometry through the local incidence angle. By using different state-of-the-art CNN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…Several SAR satellites can be used for forest monitoring [30], such as SENTINEL 1 [31], ALOS PALSAR [32], ICESat GLAS [11], ENVISAT ASAR and RADARSAT [33] and one of the most used, TanDEM-X [34]. Since September 2010, a second satellite TanDEM-X (TDX) was added to TerraSAR-X (TSX) for the acquisition of a global digital elevation model (DEM) from bistatic X-band interferometric SAR acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…Several SAR satellites can be used for forest monitoring [30], such as SENTINEL 1 [31], ALOS PALSAR [32], ICESat GLAS [11], ENVISAT ASAR and RADARSAT [33] and one of the most used, TanDEM-X [34]. Since September 2010, a second satellite TanDEM-X (TDX) was added to TerraSAR-X (TSX) for the acquisition of a global digital elevation model (DEM) from bistatic X-band interferometric SAR acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…As a future activity, we aim at further extending the proposed methodology by exploiting Sentinel-1 interferometric capability and use the coherence parameter as an additional input feature. The S-1 interferometric coherence can be indeed used for finer change detection and to perform land cover classification as in [52], together with the application of deep learning approaches [53].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [25][26] [27] [28]showed CNN and FCN were used in sementic segmentation on forest mapping. In [25] a VGG neural network (an architecture of CNN) was proposed to classify pixels with a sliding window technique.…”
Section: Cnn and Fcn In Pixel-wise Dead Forest Mappingmentioning
confidence: 99%